Peningkatan Kompetensi di Bidang Otomasi Industri Bagi Siswa SMK Jurusan Teknik Pemesinan - Priyanto, Kaleb; Kurniadi, Ninda; Baihaqi, Setyo Bhahak Fendi; Gojandra, Farda Pega Libra; Kristiawan, Ruben Bayu; Cahyanto, Septian Eko; Enita, Sarai (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
The increasing demand for skilled human resources in the field of automation by the workforce has encouraged vocational education institutions to align their graduates' competencies with industry needs. Students must be equipped with up-to-date skills in line with technological advancements. Currently, the availability of technical expertise programs in vocational high schools (SMK) that include industrial automation curricula is very limited. This situation does not align with the growing industrial demand for SMK graduates with automation competencies, such as wiring and PLC programming skills. Based on these circumstances, this automation system training based on PLC was conducted as part of a community service program. The activity aimed to enhance the skillsets of vocational high school students, particularly in the machining engineering department. The training utilized PLC-based automation systems with Omron CP1E E30-DR-A controllers. The PLC logic programming was performed using CX-Programmer software. The results of the program showed that most participants could grasp the material well. Moreover, all participants gained new insights and skills in industrial automation systems, which serve as valuable support when entering the workforce.